Proceedings of the 6th International Conference on PErvasive Technologies Related to Assistive Environments 2013
DOI: 10.1145/2504335.2504362
|View full text |Cite
|
Sign up to set email alerts
|

Towards a hierarchically-structured decision support tool for improving seniors' independent living

Abstract: In the current work, we present our position towards the modeling of a decision support system for health assessment and prevention of risky situations in the life of seniors. A two-layer architecture based on the Fuzzy Cognitive Maps (FCMs) methodology is considered as the main tool to encode medical knowledge and reason about the health status of seniors. This is the initial step, since outputs of several discrete FCM models are then combined to form the input concepts for an upper level schema (the health s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…It aims to provide an advanced and affordable health-care assistance in a smart home environment, adopting a three-layer architecture and an unobtrusive sensor network to support a Decision Support System (DSS) for providing inputs to monitoring apps by user-friendly interaction [ 23 ]. A limited set of sensors and devices, such as a wrist wearable unit, a camera, a microphone and a Kinect sensor, are used in a SH setting to identify the basic physical activities (lying, sitting, walking, standing, cycling, running, ascending and descending stairs) of elderly people [ 24 ]. A low cost off-the-self system and open source platforms are developed to facilitate the generation of applications addressing the gap between advanced technologies and aging population.…”
Section: Smart Home Projects and Applicationsmentioning
confidence: 99%
“…It aims to provide an advanced and affordable health-care assistance in a smart home environment, adopting a three-layer architecture and an unobtrusive sensor network to support a Decision Support System (DSS) for providing inputs to monitoring apps by user-friendly interaction [ 23 ]. A limited set of sensors and devices, such as a wrist wearable unit, a camera, a microphone and a Kinect sensor, are used in a SH setting to identify the basic physical activities (lying, sitting, walking, standing, cycling, running, ascending and descending stairs) of elderly people [ 24 ]. A low cost off-the-self system and open source platforms are developed to facilitate the generation of applications addressing the gap between advanced technologies and aging population.…”
Section: Smart Home Projects and Applicationsmentioning
confidence: 99%
“…SWEET-HOME, a French project, aimed at developing an assisted living technology mainly based on audio analysis [13]. Billias et al [14] adopted ambient sensors, such as cameras and microphones, to analyse the daily activities of older users. Recently, Lio [15], a personal robot assistant developed by F&P Robotics, was introduced with a multifunctional arm.…”
Section: Introductionmentioning
confidence: 99%
“…During the last few decades, many researchers have tried to carry out smart home projects [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. For instance, GatorTech [ 19 ] is an earlier smart home project that was developed at the University of Florida.…”
Section: Introductionmentioning
confidence: 99%
“…The Markov Logic Network has been a prominent approach in research on smart homes for context-aware decision processes for coping with uncertain events that are predicted from sensor data [ 22 ]. In [ 24 ], several ambient sensors such as cameras and microphones were combined to recognize elderly activities (e.g., lying, sitting, walking, standing, cycling, running, and ascending and descending stairs). In [ 25 ], the authors suggested a smart assistive living environment for facilitating the prolonged stay of elderly people at home.…”
Section: Introductionmentioning
confidence: 99%